Pengamatan Ekspresi Wajah Secara Adaptif dengan Presentasi Pemutaran Musik - Agam Pamungkas Lumintan; Liliana Liliana; Henry Novianus Palit (Jurnal Infra, 2015)
High life demands nowadays make the individual emotional state change easily. Music is one of many media that is used to stabilize a person’s emotional condition. However, wrong use of music can worsen a person’s emotional condition, as in the case of today’s society.To prevent that, an application that can detect the user’s facial expression to stabilize the user’s emotional state through music is developed. The expression on the face is determined by the position of eyebrows, eyes, mouth, and wrinkles features. The positions of detected features are compared with those in a neutral face that has been previously calibrated. The difference of features’ positions will be used as input of the trained neural network to determine the expression on the detected face.Through some experiments, the accuracy of detection of facial features and facial expressions are known. The detected expression will trigger the playback of music to stabilize the user’s emotional condition. The weakness of this application is that the music library must be set manually by the user.